Pengembangan Custom Made Signage sebagai Sarana Informasi dalam Struktur Desain Sistem Tanda di Pasar Jrakah Semarang - Abi - Senoprabowo; Muh. Ariffudin Islam (DeKaVe, 2014)
Recently, the Government of Semarang City has been providing public facilities for societyseriously. One of public facilities that is improved namely market of Jrakah. Jrakah market is one oftraditional markets in Semarang which is finished renovated for the interest of society. Visually, thedevelopment concept of Jrakah market already looks good. The problem arises when the seriousness ofgovernment in developing of public facilities only focus on phisical building. Detail of facilities andinfrastructures on Jrakah market is not considered seriously.One of problem which visible is the absence ofgood sign system as information facility for visitors, especially buyers. The Sign system which is notcommunicative can make them be confused. This research is carried out to understand effectiveness of theexisting sign system, and to propose the design of new sign system which more communicative than onesbefore on Jrakah market. To solve that problem, the sign system design method which will be used is YongkiSafanayong’s ones, that is begun from breakdowning backgrounds, identifying problem, analizing, choosingstrategy, executing, and until finishing. The result of this research is design proposal of sign system which canbe applied on Jrakah market.